A Study on the Effect of Abusive Supervision on Knowledge Hiding: Mediated by Emotional Exhaustion and Moderated by Coworkers Support - Bushra Khursheed; Um-e-Rubbab (NUML International Journal of Business & Management)
This study was conducted to assess the effects of abusive supervision on knowledge hiding, taking into account the moderating influence of coworker support and the mediating function of emotional exhaustion. The current study's model suggests that when supervisors are abusive, people become emotionally exhausted and hide knowledge. Our study proposed that employees who experienced abusive behaviors were more likely to withhold information and knowledge from others in the organization.  There was a strong association between abusive supervision and emotional exhaustion. This means that employees who experienced abusive behaviors from their supervisors were more likely to feel emotionally drained and depleted. Another purpose of the research was to know whether coworker support moderates the relationship between abusive supervision and emotional exhaustion. Coworker support may offer a sense of support and social connection, which can help employees cope with the stress associated with abusive supervision. The model was supported by Social exchange theory. Convenience sampling was used to gather data from 181 workers in the telecom sectors of firms in Rawalpindi and Islamabad. Adapted questionnaires with five-point Likert scales for each variable were used. Results indicated that abusive supervision has a positive and significant relationship with knowledge hiding. The mediating role of emotional exhaustion between abusive supervision and knowledge hiding was also supported by results. However, contrary to expectations, moderating the role of coworkers’ support, between abusive supervision and emotional exhaustion gained no acceptance. By incorporating specific training on recognizing and avoiding abusive behaviors from the outset, organizations can set clear expectations for supervisory conduct and create a culture that discourages abusive practices. Regular policy reviews will help the organization adapt to evolving challenges and best practices in preventing abusive supervision, ensuring that policies remain relevant and contribute to a positive work environment. Limitations and future directions are also provided.